Anhedonia modulates benzodiazepine and opioid demand among persons in treatment for opioid use disorder - Greenwald, Mark K.; Moses, Tabitha E. H.; Lundahl, Leslie H.; Roehrs, Timothy A. (Frontiers in Psychiatry, 2023)
Background: Benzodiazepine misuse is a significant public health problem, particularly in conjunction with opioid use, due to increased risks of overdose and death. One putative mechanism underlying benzodiazepine misuse is affective dysregulation, via exaggerated negative affect (e.g. anxiety, depression, stress-reactivity) and/or impaired positive affect (anhedonia). Similar to other misused substances, benzodiazepine consumption is sensitive to price and individual differences. Although purchase tasks and demand curve analysis can shed light on determinants of substance use, few studies have examined benzodiazepine demand, nor factors related to demand. Methods: This ongoing study is examining simulated economic demand for alprazolam (among benzodiazepine lifetime misusers based on self-report and DSM-5 diagnosis; n=23 total; 14 male, 9 female) and each participant’s preferred-opioid/route using hypothetical purchase tasks among patients with opioid use disorder (n=59 total; 38 male, 21 female) who are not clinically stable, i.e. defined as being early in treatment or in treatment longer but with recent substance use. Aims are to determine whether: (1) benzodiazepine misusers differ from never-misusers on preferred-opioid economic demand, affective dysregulation (using questionnaire and performance measures), insomnia/behavioral alertness, psychiatric diagnoses or medications, or urinalysis results; and (2) alprazolam demand among benzodiazepine misusers is related to affective dysregulation or other measures. Results: Lifetime benzodiazepine misuse is significantly (p<.05) related to current major depressive disorder diagnosis, opioid-negative and methadone-negative urinalysis, higher trait anxiety, greater self-reported affective dysregulation, and younger age, but not preferred-opioid demand or insomnia/behavioral alertness. Alprazolam and opioid demand are each significantly positively related to higher anhedonia and, to a lesser extent, depression symptoms but no other measures of negative-affective dysregulation, psychiatric conditions or medications (including opioid agonist therapy or inpatient/outpatient treatment modality), or sleep-related problems. Conclusion: Anhedonia (positive-affective deficit) robustly predicted increased benzodiazepine and opioid demand; these factors could modulate treatment response. Routine assessment and effective treatment of anhedonia in populations with concurrent opioid and sedative use disorder may improve treatment outcomes.